\[I=\int\dfrac{2xdx}{(x^2+1)(x^2+3)}\] \[let\space x=\red{\tan\theta}\Rightarrow dx=\sec^2\theta d\theta\] \[\Rightarrow I=2\int\dfrac{\tan\theta\sec^2\theta d\theta}{(\tan^2\theta+1)(\tan^2\theta+3)}\] \[=2\int\dfrac{\tan\theta\cancel{\sec^2\theta}d\theta}{\cancel{\sec^2\theta}(\sec^2\theta+2)}\] \[=2\int\dfrac{\tan\theta\red{\times\cos^2\theta} d\theta}{(\sec^2\theta+2)\red{\times\cos^2\theta}}\] \[=2\int\dfrac{\sin\theta\cos\theta d\theta}{1+2\cos^2\theta}\] \[=\int\dfrac{\sin 2\red{\theta} d\red{\theta}}{2+\cos 2\red{\theta}}\] \[=\dfrac{1}{2}\int\dfrac{\sin \red{u} d\red{u}}{2+\cos \red{u}}\] \[=\dfrac{1}{2}\int\dfrac{\red{\sin {u} d{u}}}{2+\cos {u}}\] \[=\dfrac{-1}{2}\int\dfrac{{d\red{\cos u}}}{2+\red{\cos {u}}}\] \[=\dfrac{-1}{2}\ln(| 2+\red{\cos u}|+C\] \[=\dfrac{-1}{2}\ln(|1+\red{1+\cos 2\theta}|)+C\] \[=\dfrac{-1}{2}\ln(|1+\red{2\cos^2 \theta}|)+C\] \[=\dfrac{-1}{2}\ln(|1+{\dfrac{2}{1+\red{\tan^2\theta}}}|)+C\] \[=\dfrac{-1}{2}\ln(|1+{\dfrac{2}{1+\red{x^2}}}|)+C\]
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.